(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2014)
Heparin has been in the market since the last six decades due to its potential anticoagulantÂ property. The mechanism of its anti-coagulation effect is well established. Along with itsÂ anticoagulant activity the other activity that is gathering a lot of importance now-a-days is itsÂ ability to arrest the progression of tumors specially some solid forms of tumors such as small cellÂ lung carcinoma and pancreatic tumors. The chemically modified and light molecular weightÂ fractions of heparin have been found to be more active in countering tumor progression. In thisÂ review we discuss a brief history of this versatile biomolecule with its clinical data andÂ postulated mechanism of action as per recent studies. This review also highlighted the approachÂ of heparin-conjugated nanoparticles to achieve targeted drug delivery with synergistic responseÂ in tumor cells.